1993
DOI: 10.1029/92wr02528
|View full text |Cite
|
Sign up to set email alerts
|

Solute transport through large uniform and layered soil columns

Abstract: Solute transport experiments are often conducted with homogeneous soils, whereas transport in real situations takes place in heterogeneous soils. An experiment was conducted to compare unsaturated solute transport through uniform and layered soils. Pulse inputs of tritiated water, bromide and chloride were applied under steady flow conditions to the tops of two large (0.95 m diameter by 6 m deep) soil columns. One column was uniformly filled with loamy fine sand and the other filled with alternating 20‐cm‐thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 20 publications
3
43
1
1
Order By: Relevance
“…Plotting dispersivity (Table 2) as a function of column length (Figure 3) it is seen that dispersivity increases linearly with travel distance. While scale dependence has been observed for intact and heterogeneous columns [Khan and Jury, 1990;Bejat et al, 2000], repacked columns generally do not show scale dependence [Khan and Jury, 1990;Shukla et al, 2003], with exceptions observed by Huang et al [1995] and Porro et al [1993]. The dispersivity values are generally expected to be of the order of the mean grain size [Bear, 1972].…”
Section: Ad Transportmentioning
confidence: 99%
“…Plotting dispersivity (Table 2) as a function of column length (Figure 3) it is seen that dispersivity increases linearly with travel distance. While scale dependence has been observed for intact and heterogeneous columns [Khan and Jury, 1990;Bejat et al, 2000], repacked columns generally do not show scale dependence [Khan and Jury, 1990;Shukla et al, 2003], with exceptions observed by Huang et al [1995] and Porro et al [1993]. The dispersivity values are generally expected to be of the order of the mean grain size [Bear, 1972].…”
Section: Ad Transportmentioning
confidence: 99%
“…Scotter and Tillman, 1991;Porro et al, 1993;Jabro et al, 1994) there may be potential for the ion to become sorbed to organic soil or bound or electrostatically attracted at the mineral surface (Lange et al, 1996). As a consequence, the sorption strength of the Br À ion to soil, typical of that found in the study catchment, was assessed prior to undertaking the tracer experiments.…”
Section: Assessment Of the Conservative Behaviour Of The Tracermentioning
confidence: 99%
“…Anomalous transport (despite the somewhat misleading nomenclature) is very often found at all scales -from pore scale simulations [144], soil cores [24,33,92,116], laboratory experiments [70,79,119,133], to fieldscale observations (e.g., [2,[11][12][13]45,65,83,87,143], among many others). Anomalous transport may be characterized by non-Gaussian leading or trailing edges (also called heavy tails) of a plume emanating from a point source, or nonlinear growth of the centered second moment.…”
Section: Introductionmentioning
confidence: 99%